You need to solve for x and y the following system of equations, such that:

`{(xy = 12),(1/y - 1/x = 7/12):}`

You need to start solving the second equation by bringing the terms to the left side to a common denominator, such that:

`(x - y)/(xy) = 7/12`

Since the first equation indicates that the product `xy = 12` , hence, you may substitute `12` for `xy` in the second transformed equation, such that:

`(x - y)/12 = 7/12 `

Reducing duplicate factors yields:

`x - y = 12 => x = 12 + y`

You need to substitute `12 + y` in the first equation such that:

`(12+y)*y = 12 => 12y + y^2 - 12 = 0`

`y^2 + 12y - 12 = 0 `

Using quadratic formula yields:

`y_(1,2) = (-12+-sqrt(144 + 48))/2 => y_(1,2) = (-12+-sqrt192)/2`

`y_(1,2) = (-12+-8sqrt3)/2 => y_(1,2) = (-6+-4sqrt3)`

`x_(1,2) = 12 - 6+-4sqrt3 => x_(1,2) = 6+-4sqrt3`

**Hence, evaluating the solutions to the given system of equations yields `(-6+4sqrt3;6+4sqrt3)` and `(-6-4sqrt3;6-4sqrt3).` **

## See eNotes Ad-Free

Start your **48-hour free trial** to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Already a member? Log in here.